2022
DOI: 10.35877/454ri.daengku883
|View full text |Cite
|
Sign up to set email alerts
|

Application of Vector Error Correction Model on Macroeconomic Variables toward Changes in the Composite Stock Price Index

Abstract: Macroeconomic variables are still interesting to study because some studies still find inconsistent results and dependence on the dynamics of the capital market and international financial markets, especially when there is turmoil in the domestic and international stock markets. This study aims to analyze the causality and cointegration relationship of macroeconomic variables, namely: interest rates (BI Rate), inflation and exchange rates to changes in the composite stock price index (CSPI) using the Vector Er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…The object of this research is the factors and actors that play a role in the development of IFL in Gorontalo. Research subjects are individuals who have information and are involved in IFL development efforts which we refer to as experts (Pratiwi, Wardhana and Rusgianto, 2022). The data needed in this study is primary data that comes from interviews, Focus Group Discussions (FGD), and the results of completing closed questionnaires by experts.…”
Section: Methodsmentioning
confidence: 99%
“…The object of this research is the factors and actors that play a role in the development of IFL in Gorontalo. Research subjects are individuals who have information and are involved in IFL development efforts which we refer to as experts (Pratiwi, Wardhana and Rusgianto, 2022). The data needed in this study is primary data that comes from interviews, Focus Group Discussions (FGD), and the results of completing closed questionnaires by experts.…”
Section: Methodsmentioning
confidence: 99%
“…The company's strategy is aimed at producing good company performance, especially sales, marketing and financial growth (Wardoyo, Rusdianti, & Purwantini, 2015), and general business development (Pratiwi et al, 2022). Various studies have shown that implementing the right business strategy can have a positive and significant impact on company performance.…”
Section: Business Strategymentioning
confidence: 99%
“…In the mean time, outside variables that trigger the improvement of MSMEs incorporate simple get to to credit, financial advancement, and technological advances . (Pratiwi et al, 2022).…”
Section: Msme Performancementioning
confidence: 99%